TEACHING ELEMENTARY SCHOOL PUPILS A HEALTHY LIFESTYLE THROUGH NATIONAL GAMES - Gimazutdinov Radik, Gimazutdinov Radik (Журнал иностранных языков и лингвистики, 2021)
in this article discusses teaching elementary school pupils a healthy lifestyle through national games. Because right ‘switch’ elements of games in the process of physical education is actively promoting the harmonious development and physical fitness of students.